2022
DOI: 10.1159/000525467
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Systemic Treatment Regimen for Unresectable Hepatocellular Carcinoma: Does Etiology Matter?

Abstract: NA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…18 However, this trend was not confirmed in the present study. Notably, there have been several reports stating that ICIs are more likely to be effective in NASH-HCC when combined with a molecular-targeted agent, such as bevacizumab, 19 which was consistent with the results in this study. The usefulness of the chronological measurement of AFP as a predictor of response to atezolizumab plus bevacizumab therapy has also been reported.…”
Section: Patient Characteristicssupporting
confidence: 92%
“…18 However, this trend was not confirmed in the present study. Notably, there have been several reports stating that ICIs are more likely to be effective in NASH-HCC when combined with a molecular-targeted agent, such as bevacizumab, 19 which was consistent with the results in this study. The usefulness of the chronological measurement of AFP as a predictor of response to atezolizumab plus bevacizumab therapy has also been reported.…”
Section: Patient Characteristicssupporting
confidence: 92%
“…Other previous reports have shown consistent results with our study [33,34]. Notably, a previous report stated that ICIs are more likely to be effective in NASH-HCC when combined with a molecular-targeted agent, such as bevacizumab [35].…”
Section: Discussionsupporting
confidence: 92%
“…NASH-HCC is one portion of non-viral HCC, but the exact etiology is not stated in most clinical trials, including the IMbrave050 trial. However, it has been clear that, unlike immune checkpoint inhibitor (ICI) monotherapy, Atezo/ Bev is equally effective regardless of etiology [12][13][14] in advanced HCC. Similarly, it was revealed that adjuvant Atezo/Bev was effective in curatively treating HCC in terms of suppression of recurrence in non-viral etiology.…”
Section: Results Of the Imbrave050 Trialmentioning
confidence: 99%